Risk factors for acute kidney injury in vancomycin and piperacillin/tazobactam combination therapy: A retrospective study. Issue 11 (November 2021) - Yamashita, Yuma; Kawaguchi, Hiroshi; Yano, Tsubasa; Sakurai, Norihiro; Shibata, Wataru; Oshima, Kazuhiro; Imai, Takumi; Yamada, Koichi; Nakamura, Yasutaka; Nagayama, Katsuya; Kakeya, Hiroshi
Abstract: Introduction: Combined use of vancomycin (VCM) and piperacillin/tazobactam (PIPC/TAZ) has been reported to increase the incidence of acute kidney injury (AKI). However, the risk factors associated with AKI after VCM and PIPC/TAZ (VPT) administration have not yet been identified. Therefore, we retrospectively assessed patients treated with VPT to investigate the risk factors for AKI development. Methods: The study involved patients who were treated with VPT from January 1, 2016 to March 31, 2020. The patients were divided into the AKI or non-AKI group. The clinical characteristics of patients and antimicrobial therapy were compared between the groups. Their association with AKI risk was evaluated using multivariate logistic regression analysis. Results: In total, 182 patients were included, with 118 in the non-AKI group and 64 in the AKI group. Therefore, the incidence of AKI was 35.2 %. The initiation of VPT combination therapy on the same day and concomitant use of vasopressors were associated with an increased risk of AKI (odds ratio [OR] 2.55, 95 % confidential interval [CI] 1.20–5.44 and OR 3.22, 95 % CI 1.31–7.89, respectively). Conclusion: Our findings suggest that the concomitant use of vasopressors and initiating VPT combination therapy on the same day are likely risk factors for AKI development.